2008
DOI: 10.3399/bjgp08x319431
|View full text |Cite
|
Sign up to set email alerts
|

Does distance matter? Geographical variation in GP out-of-hours service use: an observational study

Abstract: BackgroundGP cooperatives are typically based in emergency primary care centres, and patients are frequently required to travel to be seen. Geography is a key determinant of access, but little is known about the extent of geographical variation in the use of out-ofhours services. AimTo examine the effects of distance and rurality on rates of out-of-hours service use. Design of studyGeographical analysis based on routinely collected data on telephone calls in June (n = 14 482) and December (n = 19 747), and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 20 publications
4
63
2
Order By: Relevance
“…in over-riding call dispositions and translating information provided by the caller). 26 However, staff recognised the fine line between 'probing using the supporting information' and 'following the system.' We suggest that the work carried out by NHS 111 call advisers has more in common with clinical health-care work than with other generic call centre work that it superficially resembles.…”
Section: Implications Of Our Findings For Workforce Planning and Orgamentioning
confidence: 99%
See 2 more Smart Citations
“…in over-riding call dispositions and translating information provided by the caller). 26 However, staff recognised the fine line between 'probing using the supporting information' and 'following the system.' We suggest that the work carried out by NHS 111 call advisers has more in common with clinical health-care work than with other generic call centre work that it superficially resembles.…”
Section: Implications Of Our Findings For Workforce Planning and Orgamentioning
confidence: 99%
“…Typically, staff reported higher volumes of calls from certain populations, such as parents of young children and more elderly patients, consistent with the literature on out-of-hours and unscheduled care. 26 Calls were received about a broad range of issues including requests for health information (e.g. contraception advice or medication advice) or a repeat prescription.…”
Section: Types Of Calls Received By the Nhs 111 Servicementioning
confidence: 99%
See 1 more Smart Citation
“…Locations for new hemodialysis facilities resulting from the application of the model. *Municipalities served by the new center must lack a hemodialysis center of their own and also be located closer to the new center than to any other existing ones; **the number of estimated cases were calculated using prevalence data from 2008. may change rapidly because there may not exist any association between prevalence and incidence at any given time; and (iii) the use of health care increases when they become available and better situated (Turnbull et al, 2008). This has indeed been reported for renal replacement therapy (White et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Findings from a study by Turnbull et al found that patients from urban areas had higher call rates, while Campbell found those in rural areas often delayed seeking help until their own GP was available. 9,10 In England, Knowles et al found less use of the telephone service NHS Direct by certain groups within the population; men, older people, those without car or telephone, lower education levels, communication difficulties, and non-home owners in relation to their needs. 11 A study of data from the British General Household Study found higher A&E use by poorer individuals, while NHS Direct use was higher in more affluent populations.…”
Section: Introductionmentioning
confidence: 99%